PENGARUH BLANSING DAN PERENDAMAN KORO PEDANG (Canavalia ensiformis) PUTIH TERHADAP PENURUNAN HCN, SERTA KARAKTERISTIK TEPUNG DAN APLIKASINYA PADA PEMBUATAN DONAT - , PRATAMA NUR HASAN, Prof.Dr.Ir Agnes Murdiati, MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wild jack bean are local food that for as peas that have a potention for developing a flour product and processed product from flours. But the problem thet wild jack bean contain a high hidrogen cyanide (HCN) that poisonous to human body. The purpose of this research is to know the effect of blanching and soaking against HCN content on wild jack bean, determine the charateristic of wild jack bean flour, and the sensory charateristic of donuts of wild jack bean flour. The research divide into two phase, there are reduction HCN with blanching 0, 5 and 10 minutes and soaking 72 hours, making the wild jack bean flour with 5 minutes blanching and 48 hours soaking and also making of donuts using wild jack bean flours. The analysis thet use is HCN analysis, physical and chemical properties of wild jack bean flour and donuts also sensory evualuation of donuts wild jack bean. The result that soaking about 72 hours and blanching 0, 5 and 10 minutes can reduce the HCN content in wild jack bean as big as 47,7%, 67,6% and 79,7%. The wild jack bean flour have a charateristic high protein content (28,12%) low HCN content (1,62 ppm) and high degree of white. The application of wild jack bean flour for making donuts for 5% substitution preferred by panelist because its have brown colour, soft and have low jack bean flavor, and also have chemical properties protein 13,17%(db), fat 10,04%(db) and water 27,16%(wb).